Entrepreneurial learning under uncertainty: exploring the role of self-efficacy and perceived complexity. Issue 7 (7th August 2020) - Markowska, Magdalena; Wiklund, Johan
ABSTRACT: The entrepreneurial learning literature remains underdeveloped and lacks a clear understanding of the learning process. Building on an in-depth case study of four Scandinavian gourmet restauranteurs, we argue that learning to act on entrepreneurial tasks involves opening-up and focusing processes. We propose a process model that specifies how changing perceptions of complexity and self-efficacy influence an individual's preference for experimentation ( opening up ) and modelling ( focusing ) when acquiring new experience. Specifically, in situations perceived as complex, individuals will likely opt for modelling; however, individuals who feel highly self-efficacious will likely rely more on experimentation.